The impact of peer coach-led type 2 diabetes mellitus interventions on glycaemic control and self-management outcomes: A systematic review and meta-analysis. Issue 6 (December 2022) - Verma, Iksheta; Gopaldasani, Vinod; Jain, Vishesh; Chauhan, Saroj; Chawla, Rajeev; Verma, Pramod Kumar; Hosseinzadeh, Hassan
Abstract: Type 2 diabetes mellitus (T2DM) is a major health risk and dominant cause of global mortality and morbidity. Disease-specific support from peers with similar chronic condition has shown to improve chronic disease self-management outcomes. The purpose of this systematic review is to summarise the existing evidence on the impact of peer coach-led type 2 diabetes mellitus self-management interventions on glycaemic control and self-management outcomes. Databases including MEDLINE, PubMed, CINAHL Plus, Scopus, ProQuest Central, ScienceDirect, web of science, Wiley Online Library and UOW Library were searched for eligible papers. Thirteen randomised controlled trials (RCTs) published between 2008 and 2021 were included in this review. Random-effects meta-analyses found that there were statistically significant changes in Haemoglobin A1c HbA1c) after the interventions. However, the meta-analyses showed no significant changes in LDL (low-density lipoprotein), BMI (Body mass index), systolic BP (Blood Pressure), and HRQoL (Health-related quality of life) among intervention and control groups after the intervention. The identified studies mainly recruited patients with suboptimal glucose levels; majority of them belonging to low-income population. Our findings showed that peer coaching was helpful in improving HbA1c levels, quality of life, self-efficacy, diabetes distress and patient activation. Moreover, peer coaching associations with medication adherence, hypoglycaemic symptoms, diabetes specific social support and depression were inconclusive. This review concludes that peer-led community-based interventions with longer follow up, using a mixed method of delivery among patients with suboptimal levels of HbA1c were more efficient compared to usual care for improving T2DM self-management. Highlights: Disease-specific support from peers have improved diabetes self-management outcomes. Peer support is important for low-income population with poorly controlled diabetes. Peer coaching improves HbA1c levels, quality of life, self-efficacy & diabetes distress. Community based peer-led interventions are more efficient for diabetes management.